PEMBERIAN BELIS (MAHAR) PERKAWINAN PADA MASYARAKAT MANGGARAI BARAT di KECAMATAN KOMODO DITINJAU DARI HUKUM ISLAM (Studi Kasus di Desa Gorontalo Kec. Komodo Kab. Manggarai Barat Nusa Tenggara Timur) - Marniati Dwiputri Sudirman; Fathurrahman Alfa; Ach. Faisol (Jurnal Hikmatina, 2020)
Belis is a cultural dowry that must be given by a husband and given to his wife. The granting of the belis has been arranged in the customs of the Manggarai tribe, both from West Manggarai, East Manggarai, Central Manggarai. But the gift of belis (dowry) is the bride's family party who has the right to determine what kind of belis (dowry) and how many belis (dowry) that must be submitted by the bridegroom's family. Therefore it wants to interact directly with elements of society so as to get enough picture so that it can compare it with the view of Islamic law. The method used in this case study is a qualitative descriptive approach. Qualitative descriptive is a method used to draw the practice of belis that occurs in the Gorontalo community in the District of Komodo, West Manggarai Regency, NTT. Data collection was carried out in the form of observers, interviews, and documentation, then analyzed using data reduction, data presentation and verification and checking the validity of the data using credibility, transferbility, dependability, and confirmability. Keywords: Belis (dowry), Overview of Islamic Law